Prediction Academic Fraud of Accounting Students With Diamond Fraud Analysis - Abdul Rahman; Deliana Deliana; Rizki Syahputra; Listiorini Listiorini; Maymunah Ghavira (Kajian Akuntansi, 2023)
This study useful in obtain empirical evidence regarding the prediction academic fraud of accounting students at state higher education in Medan city using fraud diamond analysis.This research is expected to produce policies that will be able to prevent academic fraud at state higher education in Medan City. The data is primary data that comes directly from respondents using a questionnaire was distributed via googleform were sent directly to the respondents. Minimum sample used were 97 students majoring in accounting at state higher education in Medan city. This study used statistical analysis testing with SmartPLS (Partial Least Square). The results indicate that academic pressure and the ability to commit academic fraud have an effect on fraud academic. Opportunity and rationalization of committing academic fraud have no effect on academic fraud.Keywords : academic fraud, fraud diamond, smartpls